Investigating Reticulospinal Contributions to Tasks with Postural Demands - Santangelo, Cassandra (Université d'Ottawa / University of Ottawa, 2024)
Although early research of the reticulospinal tract suggested that its involvement in motor control was only in unconscious movements, recent studies using startle have provided evidence that it also contributes to voluntary movements. Furthermore, the anatomical and functional requirements of a task, such as the involvement of more proximal musculature and bilateral actions, may modulate the amount of reticulospinal contribution to voluntary movements. Specifically, the magnitude of the reaction time difference seen when a startle reflex is elicited (i.e., StartReact effect) can provide insight into the degree to which reticular structures are involved. It remains unknown whether the addition of a postural demand to a task increases reticulospinal drive relative to the same task without the postural demand. The present study used simple reaction time (RT) tasks to examine the effect of postural demand on the shortening of RT following a startling acoustic stimulus (SAS). In the lower limb task, participants executed two ankle plantar flexion tasks, one while seated and one while standing. In the standing task, participants needed to maintain whole-body balance following the voluntary movement whereas no postural demand of the lower limbs is present when participants are seated. In the upper limb task, participants executed two grip-release tasks, one with the forearm resting on a table, and one without forearm support. In the task without the support, participants needed to maintain the posture of the upper limb following grip-release. Auditory warning and "go" signals were used for all tasks. On 20% of trials the control "go" signal was replaced by a startling acoustic stimulus (SAS; 115 dB). The primary dependent measure, premotor RT, which was used to examine the StartReact effect, was measured using electromyography and analyzed using a linear mixed effects model. Given that the reticular system is thought to be a contributor to postural maintenance, it was hypothesized that voluntary movements with a postural demand would exhibit a larger StartReact effect than similar movements without a postural requirement. The results showed that postural demand did not result in a significant difference in RT when a startle reflex was elicited by the SAS in either the calf raise nor the grip release task. Thus, it is proposed that response complexity may have confounded postural demand in that tasks with greater postural demand are also more complex. Response complexity has previously been shown to decrease one's ability to prepare motor responses, which in turn reduces susceptibility to startle. In conclusion, postural demand did not increase reticulospinal drive, instead it is proposed that the increased response complexity led to a decreased effect of startle.
Keywords: StartReact effect; Reticulospinal; Reaction time